ANALISIS PENGUASAAN KATA KETERANGAN WAKTU â€œYIZHIâ€ DAN â€œYIXIANGâ€PADA MAHASISWA PRODI BAHASA MANDARIN UNTAN - Nonovia, Ria; Ina, Ina; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract?Yizhi? and ?yixiang? are types of time adverb that often found in Mandarin which means ?always, like that? but the usage of those two words are different and generally cannot be use simultaneously. Because of that, when using those two words, errors often occur in the use.To understand the mastery condition of student batch 2015 in the Mandarin Language program of Education Faculty UniversitasTanjungpura toward the words ?yizhi? and ?yixiang? along with the difficulties in learning it, the writer use research test method to collect the research data. Based on the result of the study shows that, when the students learn those words, there are types of the usage of the words that have been mastered , there are also several types of words that have been mastered, and there are also several words that have not been mastered properly. The writer realized that there are some students who not really understand the usage of those two words. Key words: YizhiYixiang, Mastery Condition